2021
DOI: 10.1088/1742-6596/2054/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Review of cascade refrigeration systems for vaccine storage

Abstract: Various models are already developed to achieve the refrigerating effect. Each refrigeration system has its own set of benefits and drawbacks, as well as a unique application. The vapor compression refrigeration system and the sorption refrigeration system are the two most prominent refrigeration technologies that may be utilized for a variety of purposes. In the medical profession, cascade refrigeration will be established in the storage of blood banks, plasma, vaccines, bone banks, biological fluids storage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The low temperature cycle refrigerant is isentropically compressed in processes 1-2, which is then passed through a cascade condenser where it heats the higher temperature cycle refrigerant (processes 3-4), expands in a throttling device (processes 3-4), and then continues to the evaporator (processes 4-1) to produce the necessary refrigerating effect. The compression of the high temperature cycle is a part of processes 5 and 6 [7].…”
Section: The Two-stage Cascade Refrigeration System's Operationmentioning
confidence: 99%
“…The low temperature cycle refrigerant is isentropically compressed in processes 1-2, which is then passed through a cascade condenser where it heats the higher temperature cycle refrigerant (processes 3-4), expands in a throttling device (processes 3-4), and then continues to the evaporator (processes 4-1) to produce the necessary refrigerating effect. The compression of the high temperature cycle is a part of processes 5 and 6 [7].…”
Section: The Two-stage Cascade Refrigeration System's Operationmentioning
confidence: 99%
“…Cao and Brake [22] observed that, unlike most refrigeration applications, ejectors at low temperatures are scarce, with a few works focusing on concept design, experimental investigation, and thermodynamic analysis. After reviewing different types of cascade refrigeration systems for ULT application, Kasi and Cheralathan [23] recommended configurations including an ejector. Moreover, studies for increasing the energy efficiency of these systems can be found in literature, such as Bai et al [24] .…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide surge in demand for blood products contributed to this growth, highlighting the crucial role of ULT refrigerators in ensuring the safe storage and transportation of lifesaving products. [2] Faruque et al performed a detailed thermodynamic analysis of a triple-stage vapor refrigeration system (TCRS) using HC refrigerants for ULT applications. The design and operating temperatures included the evaporator, low-temperature cycle (LTC) condensing, and midtemperature circuit (MTC) condensing types.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide surge in demand for blood products contributed to this growth, highlighting the crucial role of ULT refrigerators in ensuring the safe storage and transportation of lifesaving products. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%